“Como educar crianças feministas”: visibilidade das mulheres no ensino de História através de oficinas para o combate à violência - CAVALCANTE, Ândria Vitória Nóbrega (2022)
The current article talks about the problematic of the women’s history extinguishing in the teaching and in the historiography, and the consequences of this silencing, for example, the high indicatives of violence against the women, and the functioning of the teachers in the changing of this fierce scenery. This study also analyzes the results of ten thematic workshop, related to the gender study, that I made in six institutions of public teaching in Belém and metropolitan area. Therefore, I introduce the way the workshops, as pedagogical widgets used by teachers, have the potential to supply the absence of women’s history in the basic teaching study programs and show them as historical agents, promote debates in the classroom around of problematics gender oppressions and mainly operate directly in the women’s violence fighting and in the building of one society made over in gender equality.